PERAN MANAJEMEN HUMAS DALAM UPAYA PENCITRAAN LEMBAGA PENDIDIKAN - Mardiyah, Mardiyah; Ibnu Faruq Fauzi, Muhammad; F, Hasriyah; Humaira, Natasya; Kisman, Abida (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2023)
The presence of public relations management holds significant importance inside an educational institution, particularly in fostering favorable public perception through effective communication strategies. The present study examines the utilization of public relations management as a means of facilitating effective communication between educational institutions and the surrounding community. The objective of this paper is to ascertain the efficacy of various public relations management tactics in enhancing the reputation of elementary and secondary educational institutions. The methodology employed in this study involves the utilization of a literature review methodology. The findings of the study revealed that there were a total of five national publications, as indexed by Sinta, that examined the impact of public relations management on enhancing the reputation of educational institutions. These journals were identified through a search conducted on Google Scholar. Based on the findings of the conducted literature review, it is evident that public relations management can employ several strategies to enhance the image of educational institutions. These strategies encompass effective internal institutional coordination, community engagement, utilization of digital and print media, organizing school activities, active involvement in community initiatives, and a comprehensive understanding of the factors that facilitate or impede human resource management implementation.